Testing the Interspecific Function of Female Common Cuckoo “Bubbling” Call - Wang, Yanyi; Tian, Miao; Liu, Jingpeng; Lu, Xingyu; Møller, Anders Pape; Xia, Canwei (Frontiers in Ecology and Evolution, 2021)
Female common cuckoo (Cuculus canorous) predator-like “bubbling” calls distract host parental attention and reduce the egg rejection rate. Such “bubbling” calls are also frequently used to attract males and deter territorial rivals in intraspecies contact, and these calls are an ancestral character in many cuckoo species. Although hosts have had sufficient time to become familiar with this call and evolve anti-parasitic strategies, why are the hosts fooled by this “bubbling” call? We propose two hypotheses. The first hypothesis proposes that call variation reduces the opportunity for host species to correctly assess cuckoo tricks. In contrast, the second hypothesis proposes that the cost of behavior may prevent the antiparasitic strategy from evolving. In the study, we tested the prerequisites of these hypotheses, by investigating whether cuckoo calls vary during the day and testing whether the predator-like calls suppress bird activities. Based on field recordings from three different areas, we found high overlap in the calls generated during different periods. Oriental great reed warblers (Acrocephalus orientalis), a host species, did not show different responses toward the playback of female common cuckoo calls generated before noon or afternoon. Based on bird count data, we found that predator-like call playback is insufficient for suppressing bird activities. Therefore, none of the prerequisites were supported by our field data. We discuss the potential reasons for our findings and hope to inspire more research examining female cuckoo vocalizations.